Edukasi Simulasi Pertolongan Pertama Kegawatdaruratan Pre-Hospital Dengan Kasus Sesak Napas Pada Siswa Di SMK Hasanuddin Pare Kediri - Larasinge Sukmawati; Linda Arianti; Maditiya Nur Syafinandita; Diana Rachmania; Dhina Widayati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Shortness of breath or dispnea is one of the respiratory emergencies that is often encountered in society, including in the school environment. Students need to know first aid for shortness of breath so they can handle it well in the pre-hospital phase. The aim of this community service activity is to form a cadre of students who are able to educate themselves on first aid for shortness of breath through simulations and for service participants to know first aid for shortness of breath. The method of implementing this activity was carried out through lecture and simulation methods involving 4 cadres and 21 student participants from Hasanuddin Pare Vocational School. This activity was carried out on 10 - 12 October 2024. The service activities were carried out in 2 sessions where the first session was cadre empowerment through cadre training activities regarding first aid for shortness of breath and the second session was the presentation of material by trained cadres which was delivered to community service participants. The results of this community service activity were that trained cadres were able to deliver the material well and there was an increase in participants' knowledge and ability to provide first aid for shortness of breath after simulation education was carried out by trained cadres. Education using a simulation approach can increase students' understanding of the management of aid for shortness of breath so that they are able to provide first aid appropriately. The educational method with a simulation approach can be used as a medium for delivering information in pre-hospital first aid for cases of shortness of breath in students.